2016
DOI: 10.4049/jimmunol.1502249
|View full text |Cite
|
Sign up to set email alerts
|

The MHC Class I Cancer-Associated Neoepitope Trh4 Linked with Impaired Peptide Processing Induces a Unique Noncanonical TCR Conformer

Abstract: MHC class I downregulation represents a significant challenge for successful T cell–based immunotherapy. T cell epitopes associated with impaired peptide processing (TEIPP) constitute a novel category of immunogenic Ags that are selectively presented on transporter associated with Ag processing–deficient cells. The TEIPP neoepitopes are CD8 T cell targets, derived from nonmutated self-proteins that might be exploited to prevent immune escape. In this study, the crystal structure of H-2Db in complex with the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…MHC-I | tapasin | peptide editing | TAPBPR P eptide presentation by major histocompatibility class I (MHC-I) molecules is essential for recognition of intracellular pathogens and malignancies (1)(2)(3)(4)(5)(6). Following their transfer by the transporter associated with antigen processing (TAP) into the endoplasmic reticulum (ER), peptides are selectively loaded on MHC-I with the help of the peptide loading complex (PLC) multiprotein machinery, which consists of tapasin, ERp57, and calreticulin (7).…”
mentioning
confidence: 99%
“…MHC-I | tapasin | peptide editing | TAPBPR P eptide presentation by major histocompatibility class I (MHC-I) molecules is essential for recognition of intracellular pathogens and malignancies (1)(2)(3)(4)(5)(6). Following their transfer by the transporter associated with antigen processing (TAP) into the endoplasmic reticulum (ER), peptides are selectively loaded on MHC-I with the help of the peptide loading complex (PLC) multiprotein machinery, which consists of tapasin, ERp57, and calreticulin (7).…”
mentioning
confidence: 99%
“…We have also recently determined the crystal structure of H-2D b in complex with the first prototypic TEIPP peptide Trh4 (12). The structure revealed that the peptide takes a noncanonical peptidebinding pattern forming extensive sulfur-p interactions that contribute to the overall complex stability.…”
mentioning
confidence: 99%
“…Indeed, in contrast to all previously reported crystal structures of H-2D b epitopes, the TEIPP peptide Trh4 (MCLRMTAVM), derived from the commonly expressed cellular protein Trh4 (10,13), does not contain an asparagine at position 5 and comprises an unusually large number of sulfur-containing residues at positions 1, 2, 5, and 9. The crystal structure of H-2D b /Trh4 combined with site-directed mutagenesis analysis on peptide binding capacity revealed that Trh4 makes primary use of peptide residues p2C, p5M, and p9M for binding, interacting with specific aromatic residues in H-2D b (12). Indeed, the removal of sulfur atoms through the conservative substitutions of p2C or p5M to a-aminobutyric acid and norleucine, respectively, severely reduced the overall stability of the H-2D b complexes, indicating the importance of SH-p and van der Waals interactions for the stability of the MHC/peptide complex.…”
mentioning
confidence: 99%
“…In addition to somatic mutation-derived neoantigens, nonmutated endogenous proteins, called T-cell epitope associated with impaired peptide process neoantigens, can also act as immunogenic epitopes (van der Burg et al, 2016). A new study provided more unique structural mechanisms of the first identified T-cell epitope associated with impaired peptide process antigens derived from Trh4 proteins using crystallographic investigation, highlighting a significant advance in the search for novel immunotherapeutic targets (Hafstrand et al, 2016).…”
Section: Neoantigen-driven Personalized Immunotherapiesmentioning
confidence: 99%